Drug induced skin reactions characteristics in multifield emergency hospital - M Ya Rudyk (RUDN Journal of Medicine, 2012)
This prospective study was carried out in a period of 1 year on the basis of the multifield emergency hospital in the departments of therapy, urology and purulent surgery. On the basis of data of the screening method and the method of spontaneous messages a group of 347 patients with skin reactions, which potentially associated with the intake of medicines was highlighted in. Among them, there were 179 patients with non drug associated skin reactions and 168 patients with drug-induced skin reactions. The most common cutaneous drug reactions (CDR) were: acute urticaria, angioedema; drug toxidermia; allergic dermatitis; hemorrhagic vasculitis. Mostly СDR were caused by the following groups of drugs: b-lactam antibiotics; fluoroquinolones; drugs, improving cerebral blood flow; rentgencontrasting substances.